(3GdCef GdGbJUGOj ef efXhQ ESdGej (B/s - (3GdbVGI, eYf NGdOs ((3GQHO(B: s (3YGde GdcJH GdMOjK(B, s, 2011)
(3GdJYQja HGdCef GdGbJUGOj h eUGOQg GdeUGOQ GdGbJUGOj, GdeUGOQ GdYScQjI, GdeUGOQ GdGLJeGYjI, GdeUGOQ GdQhMjI, JUMjM GdeaGgje GdNGWFI, GdeMGaWI Ydi GdCef GdZPGFj, GdhYX HbUU GdCee GdSGHbI , JhKjb GdeYGedGJ h VHWgG, GYJeGO GdNWGH GdCNdGbj, GjbGY GdYbhHI Ydi GdeNGdajf, efY HYV GdeYGedGJ, eLGdGJ GdCef GdZPGFj, eSDhdjI GdOhdI, GdeSDhdjI GdGLJeGYjI, GdeSDhdjI GdGLJeGYjI GdeTJQcI h fXGe GdejQGKs
(3HHdjhZQGajG(B: (3U(B.153s
Keywords: (3GdEbJUGO GdESdGejs; (3GdCef GdUfGYjs; (3GdCef Gdbhejs